EFFECTS OF HUMAN RESOURCE INFORMATION SYSTEM ON PERFORMANCE OF COMMERCIAL BANKS IN KENYA: A CASE OF KENYA COMMERCIAL BANK - OPIYO, PERES ADHIAMBO; Abok, Dr. Alice (IJRDO - Journal of Business Management, 2015)
In today’s knowledge-economy, organizational success depends tremendously on theperformance of human resource management (HRM). Furthermore, Human ResourceManagement (HRM) has recently turned its concentration of knowledge sharing andstrategic workforce analysis and has been increasingly evolving into a significantcontributor on the organizational strategic management. The study sought to assess theEffects of Human Resource Information System on Performance of Commercial Banks;a case of Kenya Commercial Bank. More specifically, it aimed at examining howrecruitment, training, payroll administration and succession planning affect performanceof commercial banks and more specifically in Kenya Commercial Bank. The studyadopted a descriptive survey design. The target population of the study was all the 369staffs of Kenya Commercial bank. The researcher used stratified random samplingmethod to select the desired sample size of 148 respondents (40%) from the projectManagers, HR executives and few staffs. Data collected was cleaned, pretested,validated, and coded, summarized and analyzed using statistical package of SPSS V21.The study findings were presented using graphs, histograms, bar charts and pie charts.Conclusions were derived based on the P.value and the coefficient of determination. ERecruitment, E-Training, E-Payroll administration and E-Succession planning was foundpositive and significantly related to performance. HRIS is one of the most importantstrategic areas for the development of banks interaction with internal and externalclients besides product improvement and competition with other banks. It can be morethan a tool for following the employees’ basic demographic data and working hours. Itcan be a tool for identifying highly potential employees and directing them to areas oftheir working interest thereby enhancing performance.